A question of commitment: the status of children in Canada - Waldock, Thomas (Studies in childhood and family in Canada, 2020)
Children's rights : a question of status and recognition / Thomas Waldock -- Do Canadian education practices respect the rights of the child? / Katherine Covell -- Parenting education and support : a children's rights perspective / R. Brian Howe -- Promising policies, ambiguous practices : an exploration of the status of children in Canadian health care settings /Cheryl van Daalen-Smith, Brenda LeFrançois, and Devon MacPherson-Mayor -- Young people, justice, and children's rights in Canada : critical reflections at the edge of abeyant action / Shannon A. Moore -- Child welfare and the status of children requiring support and care / Thomas Waldock -- Assessing the rights and realities of war-affected refugee children in Canada / Myriam Denov and Maya Fennig -- The Supreme Court of Canada and the convention / J.C. Blokhuis -- More than a symbol : Canada's legal justification of corporal punishment of children / Joan Durrant -- A children's rights perspective on "wrongful life" disability medical negligence cases / Sonja C. Grover -- The extraordinary cases of J.J. and Makayla Sault / J.C. Blokhuis and Amy Smoke -- Participation rights of the child : at the crossroads of citizenship / Jan Hancock -- Canadian child and youth advocates' roles in supporting children's rights / M. Theresa Hunter -- Shaking the movers : a decade later--does our voice stick? / Judy Finlay and Landon Pearson -- A children's rights pathway to status and recognition / Thomas Waldock.